Experimental and Numerical Study on the Behavior of Energy Piles Subjected to Thermal Cycles. (23rd September 2018) - Fei, Kang; Dai, Di
Abstract : A laboratory-scale model test is conducted to improve the understanding of the effects of thermal cycles on the mechanical behavior of energy piles. The model pile is composed of cement mortar and dry sand with a relative density of 30% is used for the model ground. After applying the working load to the pile head, the pile is subjected to three thermal cycles with a magnitude of 15 ° C . The measured temperature response and mechanical behavior are analyzed and used to validate the proposed numerical approach. In the numerical analysis, the temperature variation due to thermal cycles is calculated using uncoupled heat transfer analysis. Then, the computed temperature field is used as the boundary condition in the sequence stress analysis. A series of numerical sensitivity analyses are carried out using the sequentially coupled method to investigate the long-term performance of energy piles under different soil and pile head restraint conditions. The numerical results suggest that the restraint condition at the pile head plays an important role in the mechanical response of energy piles. The ultimate pile resistance after thermal cycles does not decrease significantly. The accumulation of settlement of the free head pile and the reduction in the axial force of the restrained head pile should be considered in the design.